Synthesis, Linear, and Nonlinear Optical Properties of Phosphonato‐Substituted Bithiophenes Derived from 2, 2‐Dimethyl‐1, 3‐propanediol. Issue 34 (14th September 2017) - Freeman, Jason L.; French, David N.; Zhao, Qun; Wang, Jianwei; Zhang, Yuanli; Hamilton, Tracy P.; Lawson, Christopher M.; Gray, Gary M.
Abstract : The synthesis, linear absorption, emission spectra, and third‐order nonlinear optical (NLO) absorptions at 430 nm of two new series of chalcogenophosphonato‐substituted bithiophenes, pdP(X)T2 H and pdP(X)T2 P(X)pd [pd = OCH2 C(CH3 )2 CH2 O; T = 2, 5‐C4 H2 S; X = O, S, Se] are reported. The X‐ray crystal structures of pdP(X)T2 H and pdP(X)T2 P(X)pd (X = S, Se) have also been determined. The pdP(X)T2 P(X)pd compounds show weak intermolecular aromatic π–π interactions while pdP(S)T2H shows S–π interactions. The compounds exhibit emission at wavelengths ranging from 380–400 nm. Some of the quantum yields are significantly larger than that of 2, 2′‐bithiophene. The linear absorption spectra, emission spectra, and emission quantum yields show distinct trends with respect to the chalcogen and the number of substituents attached to the 2, 2′‐bithiophene ring. NLO transmission measurements of pdP(X)T2 P(X)pd (X = S, Se) indicate that saturated solutions of both compounds show significantly greater NLO absorption than saturated solutions of bpP(X)T2 P(X)bp (bp = 2, 2′‐biphenol, X = S, Se) do. Notably, the fluence at which the transmittance of a 0.27m CH2 Cl2 solution of pdP(Se)T2 P(Se)pd falls to 50 % is 0.2 J/cm 2 . This rivals the best blue nonlinear absorbers in literature. The excellent emission quantum yields and NLO absorptions make these compounds promising candidates for optical power limiting and as host materials for blue OLEDs. Abstract : A new series of bithiophene phosphonates was synthesized. These compounds are among the best nonlinear absorbers at rarely covered blue wavelengths. These materials also have strong fluorescence properties and may be used in both optical power limiting and OLED technologies